Adolfo Pons Romero (1914-1982) - Edixon Ochoa-Barrientos (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2019)
Adolfo Pons Romero was born in Maracaibo on May 19, 1914 and died in the same city on September 13, 1982. Doctor, university professor, unionist and writer (biographer, historiographer and scientific author). He was the son of Jaime Pons Ojeda (Maracaibo, 10/28/1877-Idem, 10/10/1958), doctor, politician, writer and one of the 12 apostles (first twelve graduates with doctoral theses in Venezuela) and Adelina Romero. He was the oldest of nine children: Jaime, Nemesio, Ramón, Elio, Yolanda, Julio, Darío and Joaquín.